MOBILITAS PERANTAU DARI KENAGARIAN ATAR KECAMATAN PADANG GANTING KABUPATEN TANAH DATAR DI KOTA PEKANBARU - Wulan Dari; Mita Rosaliza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted in Pekanbaru City. The purpose of this research is to find out what factors encourage the people of Atar Village, Padang Ganting Subdistrict, Tanah Datar District to migrate to Pekanbaru City, and to know how migrants (Atar people migrating) in choosing a job in rantau. The technique of determining samples by snowball sampling (snowball) because the snowball sample selection is done gradually. First. Researchers identify people who are thought to be able to provide information. Then this person is used as an informant to identify others as samples that can provide information, so this process lasted until the desired number of members of the sample. In this study the subject to be used as a source of information available in the research will be conducted as many as 11 people. The author uses qualitative methods with observation techniques, interviews, documentation, and literature studies to collect data and information. The results of this study found that there are two factors that influence the people of Atar village migrate to Pekanbaru City which are two factors that is the driving factor and pull factor. From some informants interviewed in general they migrated to Pekanbaru City driven by family economic factors, and to improve their family's economy. For migrants (Minang Atar People) in choosing a job in the rantau they are assisted by some who are by relatives, relatives or relatives. Because the people of Atar village have a very high solidarity. Those in the overseas generally cultivate and set their choices on the same business ie photocopy services business. Some of them started out as employees, and they were taught, until they were able to open their personal photocopies. In running this business must also have a social network, so the business can run well, and continue to grow. Because without good networking, social relations, and cooperation will not be able to run and maintain this photocopy effort.Keywords: Mobility, Social Network, Occupation of Perantau in Pekanbaru City